A global code scheduling technique using guarded PDG - Koseki, A.; Komatsu, H.; Fukazawa, Y. (IEEE First ICA³PP, IEEE First International Conference on Algorithms and Architectures for Parallel Processing, Brisbane, Australia, 19-21 April, 1995, 1995)
For instruction-level parallel machines, it is essential to extract parallelly executable instructions from a program by code scheduling. In this paper, we propose a new code scheduling technique using an extension of PDG. This technique parallelizes non-numerical programs, producing better machine codes than these created by percolation scheduling.< >